Perceptions and Dominant Factors of Blooket as a Game-based Learning Tool among Vietnamese Non-English Majored Students - Chau Thuc Quyen; Huu Chanh Nguyen (Dinamika Ilmu, 2025)
This study examines Vietnamese non-English major students' perceptions of Blooket, a game-based learning tool for English language education. Using a mixed-methods approach based on Asniza et al.'s (2021) framework, researchers collected survey data and conducted interviews to assess factors affecting student engagement. Quantitative results identified classroom control and time allocation as primary influential factors, with peer interaction and class size having moderate impact. Qualitative findings revealed students preferred blended learning approaches that integrate Blooket with traditional teaching methods. Students valued Blooket for enhancing engagement and motivation but expressed concerns about its limited ability to reinforce knowledge and its varying effectiveness across learning contexts and individual preferences. The study emphasizes that while game-based tools can improve engagement, their implementation requires careful consideration of both pedagogical and logistical factors. For optimal outcomes, educators should adopt a balanced approach that integrates digital tools with traditional methods while accounting for student preferences, classroom dynamics, and content requirements.